Changes in working memory performance in youth following concussion. (28th January 2018) - Green, Stephanie L; Keightley, Michelle L.; Lobaugh, Nancy J.; Dawson, Deirdre R.; Mihailidis, Alex
ABSTRACT: Objective : The purpose of this study was to compare the working memory (WM) performance pre- and post-concussion, and investigate the relationships between performance changes and characteristics such as self-reported symptom scores, number of days post-injury and age at injury in 10–14-year-old youth. Methods : Twenty-one youth (17 males) aged 10–14 years recruited from the community completed verbal and non-verbal WM tasks pre- and post-concussion. Performance was measured using accuracy and performance errors (false alarms and misses). Pre- and post-tests were compared using a Wilcoxon signed rank test, and effect size was determined using matched-pairs rank biserial correlation. Results : Comparisons showed lower verbal WM accuracy at post-test, greater verbal and non-verbal WM false alarm errors at post-test, and greater verbal WM miss errors at post-test (all r ≥ 0.30). Correlations between performance and characteristics revealed associations between younger youth and lower non-verbal WM accuracy and more false alarms at post-test, as well as an association among non-verbal WM miss errors, higher PCS scores and fewer days since injury at post-test. Conclusions : The current study found lower WM performance in youth following concussion. Furthermore, the findings suggest that false alarm errors may be a useful screening measure acutely post-concussion when assessing WM performance in youth.